2020
DOI: 10.1111/jonm.12992
|View full text |Cite
|
Sign up to set email alerts
|

A case‐crossover study of age group differences in objective working‐hour characteristics and short sickness absence

Abstract: Aim To investigate age group differences in objective working‐hour characteristics and their associations with short (1–3 days) sickness absence. Background Irregular working hours, that is shift work with non‐standard schedule, may influence sickness absence rates in hospital workers. Methods We collected daily working hours and the first incidence of short sickness absence from the employers’ electronic records from 2008 to 2017. A case‐crossover study compared the characteristics of the working hours 28 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 51 publications
2
26
0
1
Order By: Relevance
“…Earlier studies showed that the rate of short SA is more common among hospital workers with extended weekly working hours (5,23). In line with an earlier study among healthcare workers (23), we found that weekly working hours >40 hours increase the risk of short SA among both younger and older workers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Earlier studies showed that the rate of short SA is more common among hospital workers with extended weekly working hours (5,23). In line with an earlier study among healthcare workers (23), we found that weekly working hours >40 hours increase the risk of short SA among both younger and older workers.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, it is unclear whether age, sex, or type of work contact (part-time or full-time) play a role in the associations between working hour characteristics and short SA. Some previous studies found an increased risk of SA only among older shift workers (10) or among older employees working >40 hours/week (23). Also, a study showed that part-time workers are at higher risk of SA than full-time workers (24).…”
mentioning
confidence: 94%
“…In general, our data-driven strategy corroborated previous hypothesis-based research on the associations of working hour characteristics with SA risks. For example, quick returns, irregular working hours and night and weekend shifts were more common in clusters associated with high SA rates ( 11 , 16 ). It was also clear both quantitatively and qualitatively (see below) that the comprehensive data clusters captured novel risk characteristics that are not usually identified when analyzing pre-defined working hour characteristics separately.…”
Section: Discussionmentioning
confidence: 99%
“…The data on SA were derived from working hour records, which include dated indicators for absence due to sickness but no diagnosis ( 15 , 16 ). SA was selected as an objective register-based outcome of high interest but was not used for deriving working hour characteristics clusters.…”
Section: Methodsmentioning
confidence: 99%
“…To date, a growing body of evidence exists on the detailed working hour characteristics in the health care sector, as well as on the association of the working hour characteristics with various health-and wellbeing related outcomes [8][9][10][11][12][13][14][15][16] . For example, in the health care sector short intervals between the shifts are associated with increased risk of sickness absence 10), 11) and occupational injuries 8) , and long spells of night shifts seem to increase the risk for long sickness absence 9) , and some chronic diseases like breast cancer 17) .…”
Section: Introductionmentioning
confidence: 99%